Predictive trajectory tracking control for the USV in networked environments with communication constraints - Lei, Tao; Wen, Yuanqiao; Yu, Yi; Tian, Kang; Zhu, Man (Ocean engineering, 2024)
The trajectory tracking control problem of under-actuated unmanned surface vessels (USVs) suffering from communication constraints (network delay, packet loss, packet disorder) as well as external environment disturbance is investigated in this paper. To solve the aforementioned trajectory control problem, a nonlinear networked predictive control strategy based on the discrete sliding mode framework is proposed. Initially, using the forward Euler discretization method, a novel discrete virtual velocity control law is designed to transform trajectory tracking control into virtual velocity tracking control. Then, a sliding mode controller is suggested to suppress external disturbance of the USV. In addition, a networked sliding mode predictive control (NSMPC) scheme is proffered to guarantee active compensation of the communication constraints and stability of the trajectory tracking system simultaneously. Afterward, a theoretical analysis is given to show that the closed-loop system is uniformly bounded stable after the introduction of the digital network. Finally, extensive comparative simulation examples are provided to demonstrate the effectiveness of the proposed control strategy. •A novel discrete virtual velocity control law is designed to convert trajectory tracking control into virtual velocity tracking control.•A networked sliding mode predictive control (NSMPC) scheme is proposed to ensure active compensation of the communication delay and stability of the trajectory tracking system simultaneously.•The effectiveness of the proposed control strategy was verified through comparative numerical simulations.•Theoretical analysis shows that the closed-loop system of the proposed NSMPC strategy is stable after introducing digital networks.